Effects of epidemic prevention on the university management - Ning, Yi-zi (Advances in Social Sciences Research Journal, 2020)
The information transmission network is different from the physical contact network. It is of great significance to study the spread range of epidemic diseases by distinguishing the topological structure of perceptual information transmission network from that of physical contact disease diffusion network. SIR model is used to describe the transmission process of epidemic, and it is very important to explore the disease diffusion model which integrates perceptual transmission and disease diffusion. Furthermore, with a multi-layer network coupling the diffusion of perceptual information and the spread of disease, the relationship between different layers is the key element of the system model. Using multi-layer network to describe the system in the real world, through the introduction of individual awareness propagation mechanism, this paper studies the interaction between epidemic diffusion and awareness propagation in the framework of multiple networks, and establishes multiple policy adjustment rules to study the propagation dynamics of awareness in different networks. Considering the two-layer network, the first layer network is described as physical contact network, and epidemic diseases spread through the physical contact network, which affects the mutual transmission of information at the level of awareness network. The other layer is awareness communication network. It is an important task to study the complex interaction between human society and biological infectious diseases. In this work, we study the influence of awareness and behavior based on multiple networks on infection density. The university management should pay attention to topological structures of networks and the strategies.